Economic Regulation Assessment of Network Industries: Railway Infrastructure Management in Estonia - Uukkivi, Raivo; Koppel, Ott (Estonian Discussions on Economic Policy, 2018)
Naturally monopolistic network industries are subject to regulation of access to market and charging in order to achieve optimal use of infrastructure and avoid the abuse of monopoly power. Relatively little is known what results does such regulation genrerate and whether it achieves objectives. Literature states that due to the context-specific nature of regulatory framework, ex post analysis and practical experiments are necessary to study the impact of economic regulation. In this paper, the authors provide analysis of the results of economic regulation of railway infrastructure management in Estonia. Regulatory objectives and targets from relevant policy sources are identified and indicators compiled to monitor results. This is followed by discussion and recommendations for further research.